Implementation of the Multilevel Language Rule Development Model in Text-Based Indonesian Language Learning at SMPN West Lombok Regency - Sudika, I Nyoman; Wahidah, Baiq; Wahyuni, Wika (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to describe the development model of tiered language rules in text-based Indonesian language learning, and describe the implementation of the development model of tiered language rules learning in text-based Indonesian language learning in junior high schools. In collecting data, observation, interviews, documentation, and triangulation methods were used. The method of data analysis used a qualitative descriptive method, using content analysis techniques. This study describes the development model of tiered language rules targeted at obtaining results in the form of students' abilities in mastering language concepts gradually from mastering the smallest rules, namely spelling, continued with word order and finally sentence order. All levels of these language rules in their learning implementation are based on texts taught in Indonesian language learning in junior high schools. Learning tiered language rules refers to a systematic and gradual approach to learning Indonesian, starting from the most basic material to more complex ones. The main components in learning language rules include linguistic elements, language structure, and rules of language use. Linguistic elements include words (referential, standard, adjective, verb, adverb), phrases, and conjunctions (connecting words). Language structure relates to the arrangement and combination of linguistic elements into a correct pattern. Learning linguistic rules, especially in the context of Indonesian, involves several important stages. These stages include understanding concepts, identifying linguistic elements, applying them in texts, and evaluating understanding.